Flower Thrips in Blackberries in Florida - Oscar E. Liburd; Elena M. Rhodes; Elke Weibelzahl; Sara E. Brennen (EDIS)
Blackberry production is a small but growing industry in the state of Florida. Their numerous health benefits make them a good choice for Florida growers who want to diversify from traditional crops such as strawberries. Several potential pest insects and mites have been found on blackberries in Florida, but the two most likely to become key pests are stink bugs and flower thrips. This 3-page fact sheet provides information on flower thrips identification, monitoring, and management for blackberries. Written by Oscar E. Liburd, Elena M. Rhodes, Elke Weibelzahl, and Sara E. Brennan, and published by the UF Department of Entomology and Nematology, November 2014.